DETERMINAN KUALITAS AUDIT PADA PERUSAHAAN SEKTOR PERTAMBANGAN (Jurnal Riset Akuntansi, 2022)
The purpose of this study was to analyze the effect of audit fees. Audit tenure, and audit rotation on audit quality. This research uses agency theory and this research is a quantitative research. The data source used is secondary data in the form of the company's annual financial statements. Audit quality is measured using a dummy variable using the Big Four KAP Auditors and Non Big Four KAP auditors, audit fees are measured by Ln (natural logarithms), tenure audits are measured by calculating the number of years the same auditor engages the client, and rotation is measured by use dummy variables. The population in this study are mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020 that have been audited. Sample selection was done by using purposive sampling method by taking 30 samples. The analytical method used to test the hypothesis is logistic regression analysis. The results of this study indicate that audit fees have an effect on audit quality, while audit tenure and audit rotation have no effect on audit quality. Keywords: Fee Audit, Audit Tenure, audit rotation and audit quality